TOURISM AND TOURIST PERCEPTION IN ARIEȘENI COMMUNE, ROMANIA - Liliana PANTEA (Revista Română de Geografie Politică, 2023)
The present work represents an analysis of tourism in Arieșeni commune, through the lens of existing tourist resources and accommodation infrastructure, to which is added the assessment of the perception of residents and tourists regarding what constitutes tourism in a tourist resort of local interest, Arieșeni. To capture the tourist phenomenon, bibliographic sources (both related to the resort and of a general nature) were used and consulted, supplemented by field trips to "validate" the bibliographic information obtained. The tourist's perception was obtained through the sociological survey method, based on the questionnaire. Tourism in Arieșeni commune is based on the existing tourist resources, especially the natural ones; even though human resources are equally significant but less exploited. The perception of the surveyed people on tourism in the resort is a positive one, but through the interpretation of the questionnaire, the aspects that could be improved are also identified.